Offshoring and Volatility of Demand - Sebastian Benz; Wilhelm Kohler; Erdal Yalcin (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this paper we explore the role that demand uncertainty plays for the offshoring decision, and the role that offshoring plays for domestic volatility of employment. Offshoring is modeled as in Antràs & Helpman (2004), but we assume complete contracts. Firms are heterogeneous as in Melitz (2003). Uncertainty arises through recurring firm-specific shocks to demand. The presence of a cost of firing or hiring as in Bagliano & Bertola (2004) generates an intertemporal element to a firm's employment decision in its domestic and offshore production. In this environment, offshoring is driven by differential labor market exibility as well as by wage differences. Our most important results are: 1) If the foreign labor market features a high exibility, measured relative to its wage rate, compared to the domestic labor market, then higher uncertainty has a pro-offshoring effect. And 2), under this same condition, offshoring increases volatility in domestic employment of offshoring firms and the volatility of offshore employment of these same firms is larger than volatility of domestic employment.
Keywords: F10; F12; F16; 330; offshoring; volatility; labor market flexibility